The Influence of Digital Communication and Gen Z's Perception of Cooperatives and Islamic Banking - Endang Martini; Mehilda Rosdaliva; Salsabila Salsabila (PT. Hafasy Dwi Nawasena, 2025)
This study aims to examine Generation Z's interest in cooperatives and Islamic financial institutions in the digital era through a literature study approach. Generation Z, who were born and grew up amidst technological developments, have distinctive characteristics such as high dependence on technology, preference for fast and efficient services, and awareness of social and religious values. This study analyzes findings from various previous studies related to factors that influence Gen Z's interest in cooperatives and Islamic financial institutions. These factors include financial literacy, perceptions of service digitalization, religiosity, lifestyle, reference groups, and adoption of sharia-based financial technology. The results of the study indicate that sharia financial literacy is the main factor driving Gen Z's interest in Islamic banks and cooperatives. In addition, efficient and sharia-compliant digital services are a special attraction. The religiosity factor strengthens their preference for Islamic financial institutions, while lifestyle and the influence of social groups also shape their financial decisions. This study recommends that cooperatives and Islamic financial institutions develop innovative technology-based strategies to reach Gen Z. Efforts to improve financial literacy and promote sharia values through digital media are also suggested as effective approaches